Fish‐scale pit effects on erosion and water runoff dynamics when positioned on a soil slope in the Loess Plateau region, China. (28th July 2019) - Guo, Huili; Zhang, Binbin; Hill, Robert L.; Wu, Shufang; Dong, Qingge; Sun, Liquan; Zhang, Kuandi
Abstract: Soil moisture construction is a very important way to reduce soil erosion and maintain crop growth in arid and semiarid regions of China. A microcatchment technique for soil erosion prevention widely used on soil slopes on the Loess Plateau are fish‐scale pits (FSPs). This technique is combined with afforestation techniques to store runoff, interrupt the dynamics of soil erosion, and help mitigate frequent water deficiencies encountered by forest trees. This study investigated the effects of FSPs on soil erosion dynamics including rill formation and runoff. A three‐dimensional (3D) laser scanner was used to evaluate the erosion resistance of a 15° slope treated with FSPs arranged in a triangular pattern and the hydraulic characteristics of the flow on this slope during several intermittent simulated rainfall events. The following results were obtained. (a) The FSP‐treated slope displayed eight progressive stages of erosion: splash erosion, sheet erosion, scouring by water streams, formation of the scour pits, rill erosion, down‐slope erosion, up‐slope erosion, and collapse of the pit walls. (b) As the rainfall duration increased, the runoff velocities at various locations on the slope fluctuated, but generally, the runoff velocities were significantly higher in the down‐slope positions than for the midslope and upslope positions. When the cumulative rainfall duration reached approximately 58 min and the total rainfall reached approximately 88.5 mm, the ability of the FSPs to intercept and store runoff rapidly decreased. In the first two rainfall events, both the runoff reduction benefits (RRB) and sediment reduction benefits (SRB) were positive, but following the third rainfall event, the SRB and RRB of the FSPs were negative. The accuracy of erosion parameters extracted using the 3D laser equipment and the ArcGIS software in comparison with the measured rill erosion parameters all less than 10%. The relative error between the measured sediment and the calculated sediment is within 5.66–22.13%. (c) During the rainfall process, the flow on the upslope was constantly in the laminar regime, but after the FSPs were completely filled with water, the laminar flow on the downslope transitioned into a turbulent flow. (d) As the cumulative rainfall duration increased, the degree of topographic relief and the number of rills increased, as did the measurements of surface roughness and flow resistance. In conclusion, the microcatchment methods reduced the rill erodibility and enhanced the soil's resistance to concentrated flow erosion.